PENGARUH PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING STUDI PADA PABRIK PLASTIC ROMEN SPORT - Abdur Rosid; Jefriyan Putra Alamsyach; Syariful Allam; Ayu Lucy Larasaty (CV. ALIM'SPUBLISHING, 2023)
Businesses in various fields face increasingly fierce competition. In the face of competition, only using advanced technology in the company's production and operations is not enough. The company's use of advanced technology must be supported by reliable personnel, because no matter how sophisticated the technology used, if it is not supported by reliable personnel, it may not necessarily contribute to the smooth operation of the company. The purpose of this research is to find out and test whether compensation has an effect on employee performance, whether compensation has an effect on job satisfaction, and whether job satisfaction has an effect on employee performance. This research is included in the quantitative research using the Partial Least Square (PLS) method. The population in this study were employees of the plastic romen sport factory. The sample in this study used slovin using 55 people. The analysis technique in this research is descriptive and inferential statistical analysis using the Partial Least Square (PLS) method. The results of this study show that compensation affects employee performance, does compensation affect job satisfaction, and does job satisfaction affect employee performance?